2005
DOI: 10.1007/s10709-003-2711-7
|View full text |Cite
|
Sign up to set email alerts
|

Studying genetics of adaptive variation in model organisms: flowering time variation in Arabidopsis lyrata

Abstract: Arabidopsis thaliana has emerged as a model organism for plant developmental genetics, but it is also now being widely used for population genetic studies. Outcrossing relatives of A. thaliana are likely to provide suitable additional or alternative species for studies of evolutionary and population genetics. We have examined patterns of adaptive flowering time variation in the outcrossing, perennial A. lyrata. In addition, we examine the distribution of variation at marker genes in populations form North Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…The A. lyrata complex has already proven to be a suitable study system for the analysis of character traits such as flowering time [9,10] or pathogen defense [11]. Additionally, molecular mechanisms for the function of sporophytic self-incompatibility have been investigated [12-20], and comparative approaches to analyse sporophytic self-incompatibility in diploids versus polyploids are underway (Jørgensen, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…The A. lyrata complex has already proven to be a suitable study system for the analysis of character traits such as flowering time [9,10] or pathogen defense [11]. Additionally, molecular mechanisms for the function of sporophytic self-incompatibility have been investigated [12-20], and comparative approaches to analyse sporophytic self-incompatibility in diploids versus polyploids are underway (Jørgensen, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…In plants, the timing of flowering results from interactions between the complex network of genes that controls development (reviewed in Simpson and Dean 2002;Koornneef et al 2004) and specific environmental cues, such as day length (Lacey 1988;Olsson and Å gren 2002;Weinig et al 2002;Griffith and Watson 2005;Riihimaki et al 2005), light level (Stanton et al 2000), temperature (Eckhart et al 2004), time of snowmelt (Stanton et al 1997), nutrient level (Stanton et al 2000), and water availability (Vasek and Sauer 1971;Aronson et al 1992;Fox 1990;Bennington and McGraw 1995;Eckhart et al 2004;Franke et al 2006;Petru et al 2006). Because the optimal timing of flowering may vary tremendously across different habitats, it is reasonable to suspect that populations and closely related species should be genetically divergent in their flowering response to environmental cues.…”
mentioning
confidence: 99%
“…Because the optimal timing of flowering may vary tremendously across different habitats, it is reasonable to suspect that populations and closely related species should be genetically divergent in their flowering response to environmental cues. Indeed, many studies have demonstrated genetic divergence in flowering time in nature (Clausen et al 1940;Schemske 1984;Stanton et al 1997;Kittelson and Maron 2001;Eckhart et al 2004;Ceplitis et al 2005;Lempe et al 2005;Riihimaki et al 2005;Franke et al 2006), but unfortunately the extent to which such differentiation contributes to local adaptation often is not clear.…”
mentioning
confidence: 99%
“…Population-based analysis with a few selected populations provided the first evidence for population genetic structure at varying geographic scales [34-36]. At a more local scale and focusing on different aspects of adaptation there are numerous contributions covering A. lyrata [37-39], and comprehensive reviews have recently been presented to summarize many more aspects [1,40]. There is very limited information regarding A. arenosa , one of the most diverse evolutionary lineages in Arabidopsis [22], with only one phylogeographic-systematic study at a broad geographic scale [19].…”
Section: Introductionmentioning
confidence: 99%